Advances in applied microbiology. - Laskin, Allen I., 1928-; Bennett, J. W.; Gadd, Geoffrey M. (Advances in applied microbiology, 2004)
Advances in Applied Microbiology offers intensive reviews of the latest techniques and discoveries in this rapidly moving field. The editors are recognized experts and the format is comprehensive and instructive. Contains 12 comprehensive revies of current research in applied microbiology, including: * Bacterial Diversity in the Human Gut * Metals in Yeast Fermentation Processes * Protozoan Grazing of Freshwater Biofilms * Molecular biology of Burkholderia cepacia complex * Non-culturable bacteria in complex commensal populations.